2012
DOI: 10.1007/s00392-012-0425-5
|View full text |Cite
|
Sign up to set email alerts
|

Intimal sarcoma of the pulmonary artery with unusual findings: a case report

Abstract: Sirs:Intima sarcoma is a rare tumor often localized in the pulmonary artery. Previous descriptions can be found dating all the way back to 1923 [9].This tumor's evolvement is characterized by endoluminal growth with later vessel obstruction. This type of tumor can also originate from the heart valves and the right ventricular outflow tract. Peripheral thromboembolism is a common concomitant finding, often leading to the false diagnosis of chronic thromboembolism.The prognosis of inoperable patients with extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Several authors have reported that FDG-PET has been useful in diagnostic workup for differentiating among or staging malignant diseases and monitoring the response to treatment [ 17 , 18 ]. Among unusual findings, other authors reported case reports of patients with PAS with a lack of uptake of FDG in PET [ 19 , 20 ]. Therefore, the role of this procedure in the diagnostic workup of PAS remains controversial and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that FDG-PET has been useful in diagnostic workup for differentiating among or staging malignant diseases and monitoring the response to treatment [ 17 , 18 ]. Among unusual findings, other authors reported case reports of patients with PAS with a lack of uptake of FDG in PET [ 19 , 20 ]. Therefore, the role of this procedure in the diagnostic workup of PAS remains controversial and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…al. [6] reported a pulmonary intimal sarcoma with a lack of uptake of FDG in PET. It also revealed highly malignant cells, but its cellularity was low with marked interstitial myxoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The use of radiation therapy and chemotherapy after surgical treatment has been found to prolong survival time compared with surgery alone . Relative studies have shown that doxorubicin, and ifosfamide may be effective . Clinical trials to better understand the role of surgery, chemotherapy, and radiation therapy are difficult to carry out due to the rarity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection has been reported to decrease clinical symptoms and lengthen survival . The prognosis seems to depend on the location and vascular extension . Death is usually due to right heart failure because of obstruction of the pulmonary arteries .…”
Section: Discussionmentioning
confidence: 99%